2013
DOI: 10.1177/0017896912471045
|View full text |Cite
|
Sign up to set email alerts
|

Comparing elearning and classroom instruction on HIV/AIDS knowledge uptake and internalizing among South African and Irish pupils

Abstract: Objective: Innovative public health approaches are required to improve human immunodeficiency virus/ acquired immunodeficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…The audiences basically varied according to the community that was being addressed or the research area dealt with. HIV affected and infected people were featured mostly in the articles reviewed (Maticka-Tyndale, Wildish, & Gichuru, 2010; Nixon et al, 2013;Sodhi et al, 2011;van Zyl et al, 2014;Wanyama et al, 2012;Willms, Arratia, & Makondesa, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The audiences basically varied according to the community that was being addressed or the research area dealt with. HIV affected and infected people were featured mostly in the articles reviewed (Maticka-Tyndale, Wildish, & Gichuru, 2010; Nixon et al, 2013;Sodhi et al, 2011;van Zyl et al, 2014;Wanyama et al, 2012;Willms, Arratia, & Makondesa, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The use of electronic learning at schools to improve uptake of HIV and AIDS knowledge was identified in one study (van Zyl et al, 2014). In this study, e-learning was used as a way of ensuring that learners take interest in the knowledge they were being given about HIV and AIDS.…”
Section: Electronic Learningmentioning
confidence: 99%
“…They identified insufficient HIV knowledge and risk perceptions, as posing major stumbling blocks to HIV/AIDS prevention in South Africa. While seeking for innovative approaches, Information and Communication Technologies (ICTs) in low and middle income countries (LMICs) were considered appropriate and showed potential to provide HIV/AIDS preventative education [ 3 , 4 , 5 ]. eHealth, an emerging field at the intersection of health informatics and public health, was identified by Eysenbach [ 6 ] as a suitable method of delivering health services and information through the use of ICTs.…”
Section: Introductionmentioning
confidence: 99%
“…In the South African context, few studies have been undertaken where these factors have been investigated. The South African Medical Research Council (MRC) showed how tailoring information according to the target groups’ information needs and preferences in an eHealth intervention, better recall and understanding of HIV/AIDS knowledge was achieved by pupils in an eLearning Web-based platform compared to classroom instruction [ 4 ]. In contrast, another South African eHealth study qualitatively explored the factors that would influence ICT acceptability in the form of telemedicine solutions in healthcare settings in the rural Eastern Cape Province [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…• A estratégia educativa baseada na prevenção positiva produziu uma série de efeitos positivos nas atitudes e nos comportamentos dos jovens frente ao HIV/aids; (Givaudan et al, 2008;Huang et al, 2008;Borawski et al, 2015) O conhecimento específico sobre HIV/aids foi avaliado em todos os estudos, apresentando aumento significativo após as estratégias educativas, principalmente nas pesquisas que utilizaram comparações entre grupo intervenção e grupo controle (Brown et al, 1991;Kindeberg et al, 1994;Cartagena et al, 2006;LaChausse, 2006;Anderman et al, 2011;Van Zyl et al, 2014).…”
Section: Cl8ha23unclassified